The Phillips curve at the ECB - Fabian Eser; Peter Karadi; Philip R. Lane; Laura Moretti; Chiara Osbat (European Central Bank (ECB), 2020)
We explain the role of the Phillips Curve in the analysis of the economic outlook and the formulation of monetary policy at the ECB. First, revisiting the structural Phillips Curve, we highlight the challenges in recovering structural parameters from reduced-form estimates and relate the reduced-form Phillips Curve to the (semi-)structural models used at the ECB. Second, we identify the slope of the structural Phillips Curve by exploiting cross-country variation and by using high-frequency monetary policy surprises as instruments. Third, we present reduced-form evidence, focusing on the relation between slack and in ation and the role of in ation expectations. In relation to the recent weakness of in ation, we discuss the role of firm profits in the pass-through from wages to prices and the contribution of external factors. Overall, the available evidence supports the view that the absorption of slack and a firm anchoring of in ation expectations remain central to successful in ation stabilisation.
Keywords: E31; E52; 330; Inflation; Phillips Curve; Monetary Policy; European Central Bank